High-performance photon-driven DC motor system - Dingyi Lin; Fujin Deng; Wei Hua; Ming Cheng; Zhe Chen; Zhiming Wang (Nature Communications)
Abstract Direct current (DC) motors are crucial in drones, robotics, and electrical devices. Conventionally, the DC motor is driven by a switching electricity converter, which utilizes electrical energy to drive mechanical motion. However, the rapid on-off switching actions in the switching electricity converter would cause electromagnetic interference (EMI), impairing the functionality of drive systems. Here, we propose a photon-driven DC motor system based on photonic converter, which utilizes optical energy to drive mechanical motion, and therefore avoids EMI derived from electrical switching and immunizes against EMI during electrical energy transmission in conventional switching electricity-driven DC motor system. The operation principle and power modulation-based speed control are also presented for the proposed photon-driven DC motor system. The experiments demonstrate that the motor accurately follows the speed reference and withstands load disturbances. This innovation opens new potential for DC motor applications by improving electromagnetic compatibility.